2021
DOI: 10.18502/cjn.v20i2.6745
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of post-dural puncture headache treatment with acetaminophen-caffeine capsule and intravenous mannitol infusion: A randomized single-blind clinical trial

Abstract: Background: Post-dural puncture headache (PDPH) is a common problem after spinal anesthesia. Depending on the severity of PDPH, there are both invasive and non-invasive treatments. Caffeine has been used for the treatment of PDPH since 1949, but the administration of mannitol is a novel management to tackle PDPH. This study was conducted to compare the effectiveness of acetaminophen-caffeine and mannitol in the treatment of PDPH. Methods: We enrolled 80 patients with PDPH in the present clinical trial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Mannitol intravenously was shown to be more effective in treating PDPH than acetaminophen-caffeine capsules when these two methods were compared in a randomized clinical trial published in 2021 [ 21 ]. In another trial, intravenous mannitol was compared to intravenous hydrocortisone, which concluded that both medications are equally effective in pain relief; however, hydrocortisone had earlier onset [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mannitol intravenously was shown to be more effective in treating PDPH than acetaminophen-caffeine capsules when these two methods were compared in a randomized clinical trial published in 2021 [ 21 ]. In another trial, intravenous mannitol was compared to intravenous hydrocortisone, which concluded that both medications are equally effective in pain relief; however, hydrocortisone had earlier onset [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…This systematic review identified 16 publications assessing medical drugs for the treatment and prevention of PDPH [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. According to a retrospective assessment of medical records that included 285 patients and was published in 2013, analgesics and antiemetics, along with bed rest and IV fluids, were sufficient to manage the symptoms of PDPH in about 79% of patients [11].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Additionally, it stimulates the sodium-potassium pump and increases CSF production. 12 Both oral and IV caffeine sodium benzoate formulations may result in a transient reduction in pain scores. Oral caffeine is well absorbed, more convenient, and less expensive.…”
Section: Treatment Of Pdphmentioning
confidence: 99%
“…Caffeine is a central nervous stimulant of the methylxanthine class and is used worldwide to enhance concentration and memory [25], with first report of usage as a treatment for PDPH in 1949 [26]. Caffeine is hypothesized to treat PDPH by inducing cerebral vasoconstriction as an adenosine receptor antagonist [27,28] since adenosine receptor activation can produce downstream vasodilatory effects via its G proteincoupled receptor activity [29].…”
Section: Caffeinementioning
confidence: 99%